(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study has been conducted to analyze the production of milk from livestock using fuzzy expert system. Livestock means farm animals considered as an asset. India consists of a large amount of livestock resources such as milk. Fuzzy logic can be used to manage uncertainty in expert systems and solve problems that cannot be solved effectively by conventional methods. The main aim of fuzzy expert systems is to use human knowledge to process uncertain and ambiguous data. The objective of this paper is to implement a fuzzy logic expert system which will help to determine the suitable conditions required for the improved and increased production of milk from livestock.